2016
DOI: 10.3906/sag-1509-84
|View full text |Cite
|
Sign up to set email alerts
|

The association of papillary thyroid cancer with microcalcification in thyroidnodules with indeterminate cytology based on fine-needle aspiration biopsy

Abstract: Background/aim: Microcalcifications are generally accepted as highly specific for thyroid malignancy, especially for papillary thyroid carcinoma (PTC). The aim of this study was to determine the significance of microcalcification within nodules that were classified as being of "indeterminate cytology" (IC) according to fine-needle aspiration biopsy. Materials and methods:Patients who underwent thyroidectomy between January 2010 and 2013 were included in the study. Nodules identified as "atypia/follicular lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Standard US examination showed that 57% of the malignant lesions were hypoechoic, in agreement with literature reports [23,31]. The presence of calcifi cation in the TN studied here increased with age but was not associated with a characteristic signal of the presence of malignancy [32][33][34][35] However, neither study was later confi rmed [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…Standard US examination showed that 57% of the malignant lesions were hypoechoic, in agreement with literature reports [23,31]. The presence of calcifi cation in the TN studied here increased with age but was not associated with a characteristic signal of the presence of malignancy [32][33][34][35] However, neither study was later confi rmed [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…Nodules without macro-calcification were 1.896 times more dangerous than nodules with macro-calcification in our study ( OR : 1.921; 95% CIs:1.085–3.402). Many studies showed that micro-calcification was independently associated with malignancy 7 , 9 , 10 . However, there were fewer studies on macro-calcification in TNs.…”
Section: Discussionmentioning
confidence: 99%
“…The main component of microcalcification is calcium oxalate crystal (11). The major mechanism of microcalcification formation is as follows (12,13): i) thrombus is formed in the fibrovascular core of thyroid nodules, which develops into infarction, or necrosis of metastatic tumor cell nests in the lymph vessels occurs and triggers calcium deposit in dead tumor cells, thus forming gravel-like microcalcification. ii) The normal tumor cells in the thyroid nodules can release metabolic products and lead to dystrophic calcification of tumor cells, but such a calcification has no association with the apoptosis and necrosis of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%